Research on the Development of China-Indonesia Tourism Cooperation Under the Background of the Belt and Road–Based on the Perspective of Normalization of Public Health Emergency Management 一带一路背景下中印尼旅游合作发展研究——以公共卫生应急管理常态化为视角 - LIU Danping; FANG Hedan; WU Miaoxuan; WU Hao (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
In 2022, China and Indonesia will enter the 72nd year of diplomatic relations, and since China's Belt and Road Initiative in 2013, the relationship between China and Indonesia in the fields of humanities, economy, trade and tourism has reached a new level. Tourism cooperation between the two countries is not only an important part of the initiative, but also an important way to meet the needs of tourism development in both countries, deepen trade and economic cooperation, and promote the construction of the Belt and Road. However, the development of tourism cooperation between the two countries has outstanding problems such as security issues, insufficient depth of cooperation and single approach, while the sudden outbreak of the epidemic at the end of 2019 has dealt a heavy blow to the tourism industry of the two countries and has affected the economy and trade of them. Based on the background of the Belt and Road, this article reorganizes the background, dynamics and obstacles of China-Indonesian tourism cooperation from the perspective of the normalization of public health emergency management, and builds a new path model to promote the deepening development of tourism cooperation between the two countries based on this, with a view to becoming an important path choice to promote the optimization and upgrading of bilateral tourism cooperation between China and Indonesia.